Local buckling resistance of Pultruded FRP columns: Theoretical predictions vs. Experimental study - Tien Thuy, Nguyen (Journal of Transportation Science and Technology, 2023)
Fiber-Reinforced Polymer (FRP) in the form of thin-walled plate structures are widely used in different engineering applications due to their outstanding features such as: high strength-to-weight ratio, excellent fatigue and corrosion resistance, etc. Due to the low stiffness, design of FRP material is usually governed by deformations or instabilities, rather than strengths. The development of a technical specification for design of FRP composite structures requires the understanding on buckling behaviour of FRP components. Local buckling of pultruded FRP column is a type of structural instabilities, occurs when the compressive stress reaches to the level that form waves in the flanges or web plates, causing the plastic deformation in the fiber which ultimately reduces its strength and stiffness. This study focuses on the local buckling resistance of pultruded FRP columns by experimental work. The test data were compared to current theoretical and numerical predictions. It is found that the difference of